2022
DOI: 10.3390/su14020919
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Metal Pollution in Road Dust of Steel Industrial Area and Application of Magnetic Separation

Abstract: Pollution characteristics and ecological risks for metals in non-magnetic and magnetic road dust from steel industrial areas were investigated by applying a magnetic separation method. Metal (except for Al, Li, Ti, As, and Sb) concentrations in the magnetic road dust were 1.2 (Sn) to 7.8 (Fe) times higher than those in the non-magnetic road dust. For the magnetic road dust, the geo-accumulation index revealed a strongly to extremely polluted status for Cr, Zn, Cd, and Sb, a strongly polluted status for Mn, Cu,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Jeong et al, (2021) used the magnetic separation method for cleanup of metals viz. Cu, Zn, Cd, Ni, Cr, and Mn from road dust industrial areas [ 81 ]. It not only reduced the metal contaminants from the industrial area but also reduces waste generation.…”
Section: Different Techniques Employed For the Removal Of Hmis Fromhm...mentioning
confidence: 99%
“…Jeong et al, (2021) used the magnetic separation method for cleanup of metals viz. Cu, Zn, Cd, Ni, Cr, and Mn from road dust industrial areas [ 81 ]. It not only reduced the metal contaminants from the industrial area but also reduces waste generation.…”
Section: Different Techniques Employed For the Removal Of Hmis Fromhm...mentioning
confidence: 99%
“…Cr is widely used in many industries, including metallurgy, steel manufacturing, automobile industry, electroplating, and wood preservation, because of its anticorrosive properties [58][59][60][61]. Cr is highly mobile and has extremely toxic effects even at very low concentrations; it is classified as a Group A carcinogen element in humans [62].…”
Section: Non-carcinogenic Risk Of Ptes In Fine Road Dust (10 μM)mentioning
confidence: 99%
“…Accordingly, controlling the zinc content of the sinter is particularly important [11][12][13][14][15]. Previous studies have shown that the zinc in sintering raw materials was mainly ZnS in iron ore and ZnO or zinc ferrite in secondary resources, ZnS was oxidized to form zinc oxide and sulfate in sintering production, and a very strong reducing atmosphere was needed to reduce and remove zinc when its content was high [16][17][18][19]. The main mineral phases in the sinter with ZnO added were magnetite, calcium ferrite (SFCA), silicate and zinc ferrite [20].…”
Section: Introductionmentioning
confidence: 99%